Evaluation of a body height and weight harmony among university students - Stanislaw B. Nowak; Ihor P. Zanevskyy (Physical Education of Students)
Background and Study Aim. A harmony between the body weight and height is one of the most important sign of the right body composition. The aim of this research was to compare objective and subjective evaluations of the body weight and height correlation by university students.